Bangla to English Code Switching in Bangladeshi Commercial Cinema - Sultana, Nasreen (Stamford Journal of English, 2013)
The language of media, especially language of cinema is relatively an unexplored area in the field of academic research. In Bangladeshi commercial cinema, it is often noticed that actors switch their codes from Bangla to English while speaking. However, it should not be thought that in cinema code switching is done without any reason; rather code switching in the dialogues is designed to convey the intended meaning. Therefore, it is important to investigate the phenomenon of code switching in Bangladeshi commercial cinema from an academic point of view. This research is descriptive and qualitative in nature. Its purpose is to find out the reasons and types of code switching which are found in the commercial films of Bangladesh. For this research, data are collected from commercial Bangladeshi films and interviews have been conducted with experts from linguistics and film background. After collecting the data, they are transcribed, tabulated and analyzed in terms of the research objectives. DOI: http://dx.doi.org/10.3329/sje.v7i0.14479 Stamford Journal of English; Volume 7; Page 263-285